Nineteenth and Early 20th Century Physical Activity and Calories by Gender and Race - Scott Alan Carson (Center for Economic Studies and ifo Institute (CESifo), 2022)
When traditional measures for income and wealth are scarce or unreliable, alternative values are effective in measuring nutritional conditions during economic development. This study uses net nutrition and calories to illustrate that during the 19th and early 20th centuries that men required about 20 percent more calories per day than women. Individuals with darker complexions had greater BMRs and required more calories per day compared to fairer complexioned individuals; however, the difference was not large. Individuals born in the Great Lakes, Plains, and South required more calories per day than individuals from the Northeast and Middle Atlantic. Residence in the developing Northeast and Middle Atlantic was associated with the fewest regional calories per capita. Nineteenth and early 20th century calorie consumption was inversely related to inequality.
Keywords: Q10; Q19; N11; N51; 330; net nutrition; 19th and 20th century gender relations; 19th and 20th century race relations